Fizjokratyczna teoria podatku i jej recepcja w polskiej myśli podatkowej - Szymaniec, Piotr (Uniwersytet Wrocławski. Wydział Prawa, Administracji i Ekonomii, 2018)
The aim of the paper is to indicate the importance of the concept of Physiocrats in the history of tax thought and the practice of public levies. The question was raised whether Physiocrats only criticized the tax system existing in the 18th century in France or they have gone beyond this criticism, proposing solutions that were important in the subsequent development of taxes. The Physiocrats believed that in each case, the tax was charged to the land rent. The concept of a single tax they proclaimed was an attempt to construct a tax system characterized by transparency, simplicity and, at the same time, a fairly distribution of tax burden. This concept was implemented, however, only in three municipalities of Baden under the rule of Margrave Carl Friedrich. The importance of the Physiocrats lies in the fact that they were the first who tried to assess the impact of individual categories of taxes on the entire economy. The notion of tax shifting, which is currently in use, is derived from their analyses. Physiocracy was the most influential economic doctrine in the Polish lands at the end of the eighteenth and early nineteenth centuries, and the concept of tax proposed by this current was the basis for postulates to reduce fiscal burden imposed on the lower strata of society, especially the peasantry. Moreover, the argument based on Physiocracy served to justify the introduction of the “tenth cent gift” (ofiara dziesiątego grosza) by the Four-Year Sejm in 1789, being the first general tax which also included nobility
Keywords: physiocracy; taxes; Enlightenment; Quesnay, François (1694-1774); limits of taxation; France; Polish-Lithuanian Commonwealth; Four-Year Sejm